2016
DOI: 10.1074/jbc.m115.668673
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic FOXO1 Target Genes Are Co-regulated by Thyroid Hormone via RICTOR Protein Deacetylation and MTORC2-AKT Protein Inhibition

Abstract: Background: Thyroid hormone (TH) and FOXO1 share similar transcriptional networks. However, TH regulation of FOXO1 activity is not well understood. Results: TH decreased RICTOR acetylation and MTORC2/AKT activity by SIRT1 activation and reduced FOXO1 phosphorylation. Conclusion: TH co-regulated transcription of FOXO1 target genes via RICTOR deacetylation. Significance: Downstream metabolic effects by TH can post-translationally activate other transcription factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Although increased mitochondrial uncoupling by T 3 in BAT did not induce ROS and AMPK activity, it can increase NAD + /NADH ratio and activate SIRT1. We have previously shown that T 3 activates SIRT1 [50], a NAD + -dependent histone deacetylase that is a negative regulator of MTOR [34], in hepatocytes. Consistent with its ability to increase mitochondrial respiration and uncoupling, T 3 also increased intracellular NAD + /NADH and activated SIRT1 within 3 to 6 h in BAT and primary brown adipocytes as well as liver [50] (Figure 7(d)).…”
Section: T 3 Inhibits Mtor Activity By Amino Acid Catabolism and Sirtmentioning
confidence: 99%
See 1 more Smart Citation
“…Although increased mitochondrial uncoupling by T 3 in BAT did not induce ROS and AMPK activity, it can increase NAD + /NADH ratio and activate SIRT1. We have previously shown that T 3 activates SIRT1 [50], a NAD + -dependent histone deacetylase that is a negative regulator of MTOR [34], in hepatocytes. Consistent with its ability to increase mitochondrial respiration and uncoupling, T 3 also increased intracellular NAD + /NADH and activated SIRT1 within 3 to 6 h in BAT and primary brown adipocytes as well as liver [50] (Figure 7(d)).…”
Section: T 3 Inhibits Mtor Activity By Amino Acid Catabolism and Sirtmentioning
confidence: 99%
“…We have previously shown that T 3 activates SIRT1 [50], a NAD + -dependent histone deacetylase that is a negative regulator of MTOR [34], in hepatocytes. Consistent with its ability to increase mitochondrial respiration and uncoupling, T 3 also increased intracellular NAD + /NADH and activated SIRT1 within 3 to 6 h in BAT and primary brown adipocytes as well as liver [50] (Figure 7(d)). Interestingly, T 3 was unable to decrease MTOR activity, induce autophagy, or increase oxidative phosphorylation when SIRT1 was inhibited (Figure 8(f,g,h)), suggesting that T 3 -mediated MTOR inhibition and autophagy in BAT required SIRT1.…”
Section: T 3 Inhibits Mtor Activity By Amino Acid Catabolism and Sirtmentioning
confidence: 99%
“…An aliquot was removed, and protein concentrations were measured using the BCA kit (Bio-Rad). Western blotting was performed using a standard protocol, as described previously [55]. Primary…”
Section: Protein Extraction and Expression Analysis By Western Blottingmentioning
confidence: 99%
“…2B-D) [16,17,[25][26][27]135]. These autophagy-related genes could be regulated directly by T 3 /THR at the transcriptional level or indirectly through FOXO1 activation by dephosphorylation and deacetylation via TH-activated SIRT1 [136,137]. SIRT1 is a NAD + -dependent deacetylase activated by increases in cellular NAD + levels that serves as an energy sensor of cells to control transcriptional activity by T 3 and FOXO1.…”
Section: Th/thr Regulation Of Hepatic Autophagymentioning
confidence: 99%
“…SIRT1 is a NAD + -dependent deacetylase activated by increases in cellular NAD + levels that serves as an energy sensor of cells to control transcriptional activity by T 3 and FOXO1. Furthermore, SIRT1 mediates T 3 -induced autophagy through stimulation of expression as well as deacetylation of autophagy-related genes [136]. The master transcription factor, transcription factor EB (TFEB), regulates autophagy and lysosome-related genes may additionally be modulated by TH [44].…”
Section: Th/thr Regulation Of Hepatic Autophagymentioning
confidence: 99%